Nonperturbative study of the action parameters for anisotropic-lattice quarks - PEARDON, MICHAEL JAMES; RYAN, SINEAD MARIE (My University, 2006)
A quark action designed for highly anisotropic-lattice simulations is discussed. The mass-dependence of the parameters in the action is studied and the results are presented. Applications of this action in studies of heavy quark quantities are described and results are presented from simulations at an anisotropy of six, for a range of quark masses from strange to bottom.
PUBLISHED
Keywords: Pure & Applied Mathematics